Carrier dynamics of low-dimensional semiconductors: from quantum wells and quantum dots to resonant tunneling devices - Lopez, Andrea Naranjo (Universidade Federal de São Carlos, 2021)
This thesis aims to study heterostructures and devices that play a fundamental role in modern nanoelectronic technologies, focusing on group III-V semiconductor materials, especially arsenide-based systems, for photodetection applications. The area under discussion deals mainly with phenomena related to the effects of quantum confinement of the charge carrier energetic states that arise when the dimensionality is reduced. It is also discussed the macroscopic implications of this confinement, mainly on the optical and transport properties of the studied heterostructures. This work will address the effects of heterostructures with quantum wells and the influence of introducing quantum dots within their architecture. Beginning with polarization-resolved photoluminescence in pure GaAs quantum wells to get a first and better understanding of the properties of this basic system, especially its excitonic complexes. The results show excitons, biexcitons and trions emissions tuned by temperature, excitation power and external magnetic fields. Excitons and biexcitons show essential differences in their dependence on the external field. While the Zeeman splitting of biexcitons is monotonically dependent on the magnetic field, with a nearly constant g-factor, the behavior of the exciton energy division is not monotonous, involving a signal inversion as a function of the magnetic field. Remarkably, a trion resonance emergence in a finite magnetic field appears at low power excitation and sigma+ polarization. The non-trivial dependence of the energy levels with the external magnetic field, together with the particular polarization trion emission, denotes an intricate exciton and trion dynamics, which a set of coupled rate equations can describe. The theoretical approach used shows that a rapid spin-flip process could lead to an asymmetric spin emission and contrasting spin dynamics of the exciton complexes induced by their charge. Once the basic system has been developed and studied, the ideas and concepts in systems with more potential technological applications are related. In this context, one of the most widely investigated semiconductor devices is the resonant tunneling diode, not only because it performs optoelectronic responses strongly dependent on external parameters such as voltage, incident light and temperature, also due to the vast physical phenomena that it allows to address and study. Since excitation, accumulation, and charge transport control are the operating parameters and responsiveness of the device, it is critical to study how these three processes are intertwined. Here, the electroluminescence of these diodes has been used to investigate the dynamics and charge carrier accumulation through the combination of magneto-electroluminescence and magnetotransport measurements. Magneto-electroluminescence results shed light on blind spots where magnetotransport media are no longer effective and enabling the assessment of intrinsic charge carrier transport processes without the need to illuminate the sample. Finally, a resonant tunneling diode with an integrated InGaAs quantum dot layer is studied, seeking the benefit derived from the main characteristic of this type of diode to carry out photodetection; the sensitivity of the tunneling current to changes in the local electrostatic potential. In principle, this could lead to the detection of individual photons, i.e., photon numerical resolution. Transport, photocurrent and electroluminescence spectroscopy results reveal that the accumulation of charge carriers is maintained by the quantum dots, demonstrating that the proposed structure is susceptible to capturing individual photoexcited holes. A theoretical explanation is proposed, where the product of different voltage-dependent functions defines how the accumulation of charge carriers induced the voltage change and aims to quantify the single-photon detection process.
Dinâmica de portadores de carga em semicondutores de baixa dimensionalidade: de poços quânticos e pontos quânticos a dispositivos de tunelamento ressonante
Keywords: Semiconductors; Quantum well; Quantum dots; Resonant tunneling diode; Optics; Nanoelectronics; Semicondutores; Poços quânticos; Pontos quânticos; Diodos de tunelamento ressonante; Óptica; Nanoelectronica; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA